DIGITALISASI GAMELAN DAN PENYEBARAN NILAI ADILUHUNG BUDAYA ISLAM - Warto Warto (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This paper reveals the development of gamelan in digital form which is done in many different forms, ranging from stand-alone e-gamelan, Internet-based e-gamelan, and e-gamelan in mobile devices. Gamelan musical instruments has been a Javanese cultural identity since time immemorial. Gamelan Javanese cultural identity that has, in fact full of Islamic values. Therefore, with the digitization gamelan, this is tantamount to doing good and as a means to draw closer to Allah SWT.